Klebsiella pneumoniae Renal Abscess Syndrome: A Rare Case with Metastatic Involvement of Lungs, Eye, and Brain - Divyanshu Dubey; Fayez S. Raza; Anshudha Sawhney; Ambarish Pandey (Case Reports in Infectious Diseases)
We describe a rare case of Klebsiella pneumoniae renal abscess with metastatic spread leading to endopthalmitis, pulmonary cavitary lesions, and cerebral emboli in a 41-year-old Hispanic female with diabetes mellitus who presented with a four-to-five-day history of fevers, headache, eye pain, and vomiting. She was treated with IV antibiotics and made a gradual but full recovery.